Electrostatic Complementarity of T-Cell Receptor-Alpha CDR3 Domains and Mutant Amino Acids Is Associated with Better Survival Rates for Sarcomas. (20th April 2021) - Yeagley, Michelle; Chobrutskiy, Boris I.; Gozlan, Etienne C.; Medikonda, Nikhila; Patel, Dhruv N.; Falasiri, Shayan; Callahan, Blake M.; Huda, Taha; Blanck, George
Abstract: While sarcoma immunology has advanced with regard to basic, and even some applied topics, this disease has not been subject to more recent immunogenomics approaches. Thus, we assessed the immune receptor recombinations available from the cancer genome atlas (TCGA) sarcoma database via tumor sample exome and RNASeq files. Results indicated that recovery of T-cell receptor-alpha recombination reads (TRA) correlated with a better survival rate, with the expression of T-cell biomarkers, and with tumor sample apoptosis signatures consistent with the longer patient survival times. Furthermore, samples representing TRA complementarity determining region-3 (CDR3) net charge per residue (NCPR) based complementarity with the corresponding sarcoma mutanome had a better survival rate, and more granzyme expression, than samples lacking such complementarity. By specifically using RNASeq-recovered TRA CDR3s and related NCPR assessments, three genes, TP53, ATRX, and RB1, were identified as being key components of the mutanome-based complementarity. Thus, these genes may represent key immune system targets for soft tissue sarcomas. Also, several key results from above were reproduced with a pediatric osteosarcoma dataset, work that led to identification of MUC6 mutations as potentially linked to a strong immune response. In sum, TRA CDR3s are likely to be important prognostic indicators, and possibly a beginning tool for immunotherapy development strategies, for adult and pediatric sarcomas.